What is the connection between Gen Y employees' loyalty, satisfaction, and workplace spirituality? - Nurhasan, Rohimat; Suwatno, Suwatno; Ahman, Eeng; Suryadi, Edi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
Maintaining and enhancing employee loyalty and satisfaction has always been a top priority for management in every firm. This study aims to investigate the relationship between workplace spirituality, loyalty, and Generation Y employees at private organisations in Indonesia. A quantitative approach with descriptive and verification analysis techniques is used to see the picture and examine the relationship between variables. Data and information were obtained from a sample of 132 people, through the process of distributing questionnaires and surveys. Data analysis using statistical software calculation tools. The results showed that each variable has a fairly high criterion. Employee loyalty is significantly influenced by workplace spirituality and job satisfaction. The results demonstrate that workers who uphold spiritual principles at work are more likely to desire to remain with the company. The theoretical contribution of this study is that Generation Y employee loyalty can be increased by increasing job satisfaction and workplace spirituality. The growth of spiritual values needs to be supported by creating a spiritual work environment, providing fair remuneration is expected to foster loyal attitudes and behavior of employees. Research is limited to Y-generation and to objects in private tertiary institutions in Garut Regency where there is a possibility of cultural similarities, therefore further research is suggested with a wider scope.